2022
DOI: 10.3389/fcimb.2022.860589
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Vaginal Microbiome Changes and Bacterial Vaginosis Plus Vulvovaginal Candidiasis Mixed Vaginitis Prognosis

Abstract: Mixed vaginitis is the result of the simultaneous presence of different pathogenic processes mediated by at least two types of vaginal pathogens. Among the various types of mixed vaginitis presentations, bacterial vaginosis (BV) plus vulvovaginal candidiasis (VVC) presents to be the most prevalent form. Mixed vaginitis affects the health of women of all ages worldwide. However, few studies have focused on clinical manifestations, pathogenesis, diagnostic criteria, or therapy of mixed vaginitis. We recruited 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Many studies also demonstrate that CVM is associated with disease treatment outcomes. For example, some studies reveal that low baseline Lactobacillus (Xiao et al, 2022), L.iners. (Zhou et al, 2022), high G.vaginalis and A. vaginae (Bradshaw et al, 2006;Ferreira et al, 2017) was associated with BV treatment failure and recurrence, although some reports show inconsistent effect.…”
Section: Normal Cervicovaginal Microbiomementioning
confidence: 99%
“…Many studies also demonstrate that CVM is associated with disease treatment outcomes. For example, some studies reveal that low baseline Lactobacillus (Xiao et al, 2022), L.iners. (Zhou et al, 2022), high G.vaginalis and A. vaginae (Bradshaw et al, 2006;Ferreira et al, 2017) was associated with BV treatment failure and recurrence, although some reports show inconsistent effect.…”
Section: Normal Cervicovaginal Microbiomementioning
confidence: 99%
“…Nevertheless, the signs and symptoms of mixed vaginitis are often atypical, and treatment is complicated in contrast to single-type vaginitis ( 20 ). Owing to differences in race, region, detection technology, and methods, the incidence of mixed vaginitis is reported to vary greatly, from 4.44 to 35.06% ( 20 , 21 ); meanwhile, the result in our study was 14.37%, of which BV combined with AV was the most common type (66.37%). Currently, little is known about the vaginal pathophysiology of mixed vaginitis.…”
Section: Discussionmentioning
confidence: 53%
“…Currently, little is known about the vaginal pathophysiology of mixed vaginitis. Studies have found that there were synergistic effects between different pathogens, allowing them to form multi-strain biofilms and to further lead to refractory infections and recurrences ( 21 , 22 ). Bacteria and/or fungi can coexist within a host and influence each other via synergistic or antagonistic interactions ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mixed vaginitis is a group of vaginal infections caused by the coexistence of two or more vaginal pathogens, leading to abnormalities in the vaginal microenvironment and causing different signs and symptoms ( Paavonen and Brunham, 2018 ; Xiao et al., 2022 ). Depending on the vaginal pathogen, they can be further categorized into more than 10 types.…”
Section: Introductionmentioning
confidence: 99%